(untitled) - Kenney, Martin (New Haven and London, 1986)
In the first serious history of the biotechnology industry, Martin Kenney examines its growth and structure, describes the role of university departments of basic and applied biology, and shows how the relationship undermines the educational role of the university.
Keywords: Công nghiệp công nghệ sinh học,Biotechnology industries